ETHNOMATHEMATICAL EXPLORATION IN THE ARCHITECTURE OF THE ICONIC BUILDING OF SOPO PARTUNGKOAN CITY OF TARUTUNG: EKSPLORASI ETNOMATEMATIKA PADA ARSITEKTUR BANGUNAN IKONIK SOPO PARTUNGKOAN KOTA TARUTUNG - Dhevy Kartika Ayu Angkat; Asrul (SOSIOEDUKASI, 2025)
The concept of mathematics will always be found in daily life. The concept of mathematics is then associated with a culture, so it is called Ethnomathematics. Ethnomathematics is one of the scientific research methods that connects an ethnicity with mathematical concepts, this research contains an exploration of what mathematical elements are found in the architecture of the iconic building of Sopo Partungkoan Tarututung City. The purpose of this research is to find out the mathematical elements that exist in the architecture of Sopo Partungkoan. This research is a type of descriptive qualitative research that obtains data sources through observations, documentation and interviews related to the Sopo Partungkoan building. This research was carried out at the Sopo Partungkoan Building, Tarutung City in April 2025. The results of this study show that the architecture of the sopo partungkoan building contains a lot of mathematical elements including, Triangle, square, rectangle, parallelogram, circle, coherence and congruence, reflection and fibbonaci concept